Proposed mechanism for the formation of dust horizons on bauxite residue disposal areas - Klauber, Craig; Harwood, N.; Hockridge, R.; Middleton, C. (2017)
Without some form of mitigation control bauxite residue disposal areas in Mediterranean climates can be subject to large-scale dust lift-off events during summer, with significant environmental impact. Intuitively dust formation relates simply to the process of drying. However, whilst wet solids will not produce dust, the converse is not always true. Both the rate of drying and the composition of the bauxite residue are critical factors in determining whether a potential dust event will occur. In this work a dust formation mechanism is proposed in which caustic salts transport and effloresce along with a changing phase composition in the brine solids from sodium bicarbonate through to trona and then to carbonate monohydrate. The efflorescence leads to a white dust event, but the carbonate phase change and the associated reduction in sodium molar volume critically breaks inter-particulate bonding between the residue particles leading to a more severe underlying red dust event.